Gospodarski razvoj Goriške in Nove Gorice ter selitvena gibanja (1945-1969) - Rendla, Marta (Dve domovini, 2023)
After World War II, the economic development of Goriška and Nova Gorica focused on strengthening industry in line with Yugoslavia’s general orientation toward accelerated industrialization. The first reconstruction period (1947–1956) saw growth on the foundations of modest prewar industry and crafts. Later, in 1957–1969, the emphasis was on overcoming the earlier development anomalies, on creating a more harmonious and diversified development, in which the previously neglected economic sectors (agriculture, construction, transport, trade, crafts, tourism) took priority, and on more quickly developing the new industries that emerged after the war. As a result of severing ties with the Italian political and economic unit and acceding to Yugoslavia, the territory and economy of Goriška experienced significant migratory dynamics. This migration influenced and shaped the post-war development of Goriška’s economy and the newly founded Nova Gorica—the new administrative-political, economic, and cultural center of Goriška.
Keywords: economic development; Gospodarski razvoj; Industrializacija; industrialization; Izseljevanje in priseljevanje; migration